Kualitas Pelayanan Administrasi Pertanahan Di Kantor Pertanahan Kabupaten Enrekang - Anugrah, Anugrah; Fatmawati, Fatmawati; Sudarmi, Sudarmi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
ABSTRACTThis study purposed to find out the quality of land administration services at the land office of Enrekang Regency. This study used qualitative with descriptive type. The number of informants in this study were 7 people by collecting data through interviews, observation and documentation. The results of the study showed that the quality of service including tangible aspects had fixed, it seen from several indicators including: facilities and infrastructure, office facilities and rules, the reliability aspect had been fulfilled in terms of the reliability of officers and reliable methods, the responsiveness aspect had been fulfilled in several ways. indicators include: the ability of officers, the way of informing informants and the approach of the officers, the assurance aspect had been fulfilled seen from several indicators including: work culture, public safety rules and employee sanctions for violating SOPs, the empathy aspect had been fulfilled seen from several indicators below. These included: Firm Attitude in Service, Firm Attitude to Employees and the response of officers to community complaints. As for the supporting factors, namely utilizing technological developments for employees and the community, which were supported by mobile applications, the Tanahku application on Google had made easier for the public to check files. Keywords: Quality of Service, defense administration